Pengaruh Financial Leverage terhadap Financial Performance pada Sektor Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2015 - Rivaldy Februansyah; Ika Yanuarti (Universitas Multimedia Nusantara, 2017)
The manufacturing sector is one of the most dominant economic sectors in in achieving growth and development in Indonesia. It needs adequate fund to develop its business. The sources of fund are from internal and external. The firm usually optimized the usage of internal fund prior to external fund. The internal fund comes from equity while the external funds are from debt and stock. Debt is also known as financial leverage. There is a phenomenon that the usage of debt increased the firm’s financial performance, since interest on debt could lower the payment of tax (tax shield). On the other side, the higher the financial leverage the higher the risk of bankruptcy. This research aims to analyze whether financial leverage has an influence on financial performance in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) period 2015. The method of analysis used in this research is multiple linear regression analysis. This research uses quantitative approach with a sample of 140 listed companies in the manufacturing industry. The firm’s financial performance could be measured by the financial ratios. Financial Leverage ratios are ratios that measure the ability of firm’s to meet its financial obligation and the level of usage debt as compared to equity. There are several financial leverage ratios that used in this research, such as Debt Ratio (DR), Debt to Equity Ratio (DER), Interest Coverage Ratio (ICR), and Long Term Debt Ratio (LTDR). Financial performance indicates the ability of firm to generate profit and measured by Profitability Ratio. Return on Asset (ROA) is one of the Profitability Ratio. The statistical result shows that Debt Ratio (DR) negatively affect Return on Asset (ROA) and Interest Coverage Ratio (ICR) positively affect Return on Asset (ROA). Meanwhile, Debt to Equity Ratio (DER) and Long Term Debt Ratio (LTDR) did not affect Return on Asset (ROA). On the other hand, result shows that Debt Ratio (DR), Debt to Equity Ratio (DER), Interest Coverage Ratio (ICR), and Long Term Debt Ratio (LTDR) affect Return on Asset (ROA) simultaneously. Keywords: Financial Leverage, Debt Ratio (DR), Debt to Equity Ratio (DER), Interest Coverage Ratio (ICR), Long Term Debt Ratio (LTDR), Financial Performance, Return on Assets (ROA)